Product Development of Anti Acne Gel: Combination of White Turmeric Rhizome Ethanol Extract (Curcuma Mango Val) and Galangal Rhizome Ethanol Extract (Alpinia Galanga) - Imron Wahyu Hidayat; Retna Tri Astuti; Tiara Mega Kusuma (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
White turmeric rhizome (Curcuma mango Val) and galangal rhizome (Alpinia galanga) have been widely studied to have antibacterial activity. One of the causes of acne is bacteria, such as Staphylococcus epidermidis. The purpose of this study was to determine the minimum inhibitory concentration of the ethanol extract of white turmeric (Curcuma mangga Val) and galangal (Alpinia galanga) rhizome against acne-causing bacteria and its effectiveness after it was formulated in gel form. Simplicia was extracted by maceration method using ethanol 96% solvent. The extract was formulated in the form of a gel with various concentrations of CMC Na. The results of the gel antibacterial evaluation showed that the ethanol extract gel of white turmeric rhizome (Curcuma mangga Val) and galangal rhizome (Alpinia galangal) showed antibacterial activity against S. epidermidis bacteria.